Weight management practices of adults in a work site setting - S. Y., Chai; Kandiah, Mirnalini (Nutrition Society of Malaysia, 2008)
Healthy diet and physical activity are recommended to control body weight and thus reduce the overweight or obesity rates in populations. The purpose of this study was to determine weight management practices, barriers and readiness to change among adults in a worksite setting. A cross-sectional survey among 100 UPM employees aged 20-61 years was conducted. Height and weight were measured to compute BMI. The prevalence of overweight and obesity were 29.0% and 13.0% respectively. About 43% of respondents thought that they were overweight or obese while 55% were trying to lose weight. The respondents had tried an average of two types of weight management methods i.e. physical activity (2.23±1.26), dietary fat reduction (1.91±1.45), increasing fruits and vegetables consumption (1.85±1.40) and reducing portion size (1.63±1.13). However, 69% of respondents thought that ‘lack of time’ was an important barrier that caused them to fail in their weight management endeavours. By stages of readiness to change for weight management, 12% of the respondents were in the pre-contemplation stage, followed by contemplation (11%), preparation (18%), action (23%) and maintenance (36%). Chi-square tests showed significant relationships between the practice of portion size control and age (p<0.05), marital status (p<0.05), occupation (p<0.01), income (p<0.05) and body mass index of respondents (p<0.05); between reducing dietary fat practice and age (p<0.05), occupation (p<0.01) and income (p<0.05); and between the practice of increasing fruit and vegetable intake and gender (women) (p<0.05) and occupation (academic) (p<0.05). Attainable weight management goal was significantly associated with stages of change (p<0.05) and gender of respondents (p<0.01). Interventions to reduce overweight and obesity in worksite populations should emphasise on teaching employees practical strategies for food portion size control, and dietary fat reduction, increase fruit and vegetables consumption and to set an attainable weight management goal